Edukasi Kompres Hangat Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif di PMB Pera Simalingkar B Medan Tuntungan Tahun 2023 - Imran Saputra Surbakti; Kamelia Sinaga; Rumondang Sitorus; Asnita Sinaga; Agustina Tumanggor; Rosmani Sinaga (STIKes Ibnu Sina Ajibarang, 2023)
Warm water compresses given to a woman's lower back in the area where the fetal head presses on the spine will reduce pain, heat will increase circulation to the area thereby correcting tissue anoxia caused by pressure. This study aims to determine the effect of warm compresses on reducing labor pain during the first active phase. This type of research is Quasi experiment, which is research that is used to determine whether or not there are consequences of